Evaluation on performance and environmental impacts of the revived industrial lead-acid batteries - Ibrahim, Noor Saidatul Maya (2022)
In Malaysia, various types of batteries have evolved, as the energy revolution from internal combustion engines to electric motors continues to progress due to increased environmental awareness. The lead-acid battery is one of the preferred choices to run the electric motor for industrial applications, such as electric forklifts and golf carts. However, the problem with lead-acid batteries is that their performance degrades over time, as the internal resistance of the battery increases due to the presence of lead sulphates (PbSO4) . Low-capacity batteries are recycled through the pyrometallurgical method contributing to carbon emissions (kgCO2e). As an alternative, regeneration technology has been introduced to revive low-capacity batteries using high-current pulses of up to 450 A to dissolve lead sulphates on the plates. The results from the experimental work that has been conducted, this technology can enhance battery capacity up to 96% and can also improve battery longevity. Using the life-cycle assessment (LCA) method, this study evaluated the carbon footprints (kgCO2e) of recycling and reviving lead-acid batteries. The carbon footprints (kgCO2e) were evaluated gate-to-gate with a functional unit of 1,315 kg lead-acid batteries. The findings from SimaPro simulator software show that recycling a lead-acid battery generated 131% more carbon footprints (kgCO2e) than from reviving it. Besides that, the process and environmental costs of both methods were compared using the environmental life-cycle costing (E-LCC) approach. The comparative results from the SimaPro simulator software show that reviving lead-acid batteries was 79% more economical than recycling them. Lastly, in response to environmental awareness, this study proposed a policy framework for lead-acid battery distribution and waste management to assist in handling the batteries.